Дослідження впливу форми пор на тепловий опір пористих теплоізоляційних матеріалів - Чейлитко, Андрій Олександрович; Чейлитко, А. А. (НТУ "ХПІ", 2016)
Рассмотрено влияние формы пор на теплопроводность пористого теплоизоляционного материала. Для исследования использовано метод компьютерного моделирования. В качестве формы пор было использовано эллипс. В течении эксперимента угол наклона пор изменялся по отношению к тепловому потоку от 0° до 90°, с шагом в 10°. В ходе исследований было обнаружено, что при размере пор 7 мм, изменение теплового сопротивления от формы пор не значительно и не превышает 1,38 %. Следовательно, улучшение пористых теплоизоляционных материалов не возможно путем варьирования формой пор, при условии небольших размеров этих пор.

The influence of pores form on the thermal conductivity of porous insulation material was learned. For research was used computer modeling method. The ellipse was used as a form of pores. During the experiment angle have been changing in relation to the heat flow from 0° to 90°, with step of 10°. It was found that with a pore size of 7 mm, the thermal resistance is changing from the pores form less than 1.38 %. Therefore, improvement of heat insulating porous material is not possible by varying the form of pores, in materials with small pore size.
Feasibility study of the thermal conductivity of metals change by changing the size and location of pores
Keywords: коефіцієнт теплопровідності; теплоізоляційний матеріал; функція Mesh; термічний опор матеріалів; теплоізолюючий матеріал; сітка